Teaching Dental Drawings for Freshman Dental Students and Its Correlation with Manual Dexterity - Elgendy, Hanan; Cui, Xiaoxi; Watkins, Todd; McQuistan, Michelle (International journal of dentistry, 2023)
Objective. To assess whether the implementation of teeth drawing exercises in a dental anatomy course improves first-year (D1) dental students’ understanding of tooth morphology, their dexterity, and their clinical skills compared with D1s who did not participate in the drawing exercises. Methods. In 2020, a “Teeth Drawing Module” was implemented within the D1 dental anatomy curriculum. In this course, students learn how to draw accurate outlines of teeth. The students are required to complete two types of drawing projects. Illustrations and instructions of teeth drawings that are outlined in a manual drawing book, PowerPoint presentations, illustration videos, and assessments are provided. Students’ grades in the drawing module, waxing skills assessments, and their didactic exams were used to evaluate and assess the correlation between their drawing aptitude and their manual skills. Students who took the drawing course were compared with students who did not take the drawing course to determine if the drawings improved students’ understanding of tooth morphology, their dexterity, and their clinical skills. A comprehensive survey was also developed and distributed to students who had the drawing module in their curriculum. Results. Students who participated in the drawing module were more successful in the dental anatomy course compared with students in the control classes. Classes that had drawing exercises scored significantly higher in all dental anatomy waxing exercises compared with classes that did not have drawing exercises (p<0.001). There was a significant positive correlation between drawing and waxing scores (p<0.05). Moreover, there was a significant positive correlation between drawing and didactic scores (p<0.001). Conclusions. Drawing exercises can be useful instruments for effectively representing and integrating the spatial domain of anatomical information. Teeth drawings as an adjunctive tool offer excellent visualization and allow students to improve their manual dexterity and knowledge in the dental anatomy course.